2019
DOI: 10.1126/scitranslmed.aav8375
|View full text |Cite
|
Sign up to set email alerts
|

In utero gene editing for monogenic lung disease

Abstract: Monogenic lung diseases that are caused by mutations in surfactant genes of the pulmonary epithelium are marked by perinatal lethal respiratory failure or chronic diffuse parenchymal lung disease with few therapeutic options. Using a CRISPR fluorescent reporter system, we demonstrate that precisely timed in utero intra-amniotic delivery of CRISPR-Cas9 gene editing reagents during fetal development results in targeted and specific gene editing in fetal lungs. Pulmonary epithelial cells are predominantly targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 53 publications
2
62
0
1
Order By: Relevance
“…Recently, two more in vivo approaches for genome editing have been reported. One of the approaches involves in utero gene delivery into postimplantation fetuses, an approach used by a group that has demonstrated the efficacy of an intraamniotic injection (as shown in b on day 12.5 in Figure 1; the day when copulation plug is found is defined as day 0 of pregnancy) of rAAVs carrying genome-editing-related genes in the successful rescue of fetuses with lethal mutations [17]. The other approach involves tail-vein injection of a solution containing a plasmid (that confers expression of both Cas9 and gRNA) into a pregnant female at the mid-gestational stage.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, two more in vivo approaches for genome editing have been reported. One of the approaches involves in utero gene delivery into postimplantation fetuses, an approach used by a group that has demonstrated the efficacy of an intraamniotic injection (as shown in b on day 12.5 in Figure 1; the day when copulation plug is found is defined as day 0 of pregnancy) of rAAVs carrying genome-editing-related genes in the successful rescue of fetuses with lethal mutations [17]. The other approach involves tail-vein injection of a solution containing a plasmid (that confers expression of both Cas9 and gRNA) into a pregnant female at the mid-gestational stage.…”
Section: Figurementioning
confidence: 99%
“…In these experiments, viral vectors, such as AAVs, lentiviruses, and adenoviruses have been involved in infecting the fetuses at days 9-15 of pregnancy. Experiments using in utero gene delivery of genome-editing components have been performed by several research groups [17,[91][92][93][94]. Ricciardi et al [93] demonstrated that intra-amniotic administration of polymeric, biodegradable nanoparticles derived from poly (lactic-co-glycolic acid) containing triplex-forming peptide nucleic acids and donor ssDNAs into mouse fetuses carrying mutations in the β-globin gene, results in the offspring being rescued from a disease similar to human β-thalassemia.…”
Section: In Utero Gene Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly speaking, they use one of two major pathways (9): non-homologous end-joining (NHEJ), often leading to small insertions or deletions (indels); and when a template is available, homology directed repair (HDR), resulting in precise correction of disease-causing mutations. Several fluorescence-based reporter systems for monitoring the outcomes of genome editing have been described (10)(11)(12)(13)(14)(15)(16)(17). However, these are predominantly in vitro reporters, relying on transiently transfected constructs or stable cell lines, or where available in vivo are limited to the detection of NHEJ events (14,15).…”
Section: Introductionmentioning
confidence: 99%